(untitled) (Wageningen (Netherlands), 1993)
The book is arranged in broad thems: 1) Looking at the landscape; 2) Identifying problems and seeking solutions: The farmers' way, by experimental work on fertility management, by attempts at land evaluation, by modelling; 3) Environmental management
Keywords: Acid soils,Soil science